2007
DOI: 10.1136/emj.2005.027730
|View full text |Cite
|
Sign up to set email alerts
|

The Bradford Burn Study: the epidemiology of burns presenting to an inner city emergency department

Abstract: Emergency departments manage patients with burns well, and referrals to plastic surgery departments are appropriate. The majority of burns can be prevented by addressing educational issues and vulnerable sections of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 10 publications
6
22
0
Order By: Relevance
“…Various international studies showed male predominance which is also in contrast with our studies. 8,[9][10][11][12][13] Most of the burn victims (66%) in our study were from rural area and this finding is in accordance with the various other studies. 2,3,6 This could be attributed to low standard of living in rural people and related factors.…”
Section: Discussionsupporting
confidence: 91%
“…Various international studies showed male predominance which is also in contrast with our studies. 8,[9][10][11][12][13] Most of the burn victims (66%) in our study were from rural area and this finding is in accordance with the various other studies. 2,3,6 This could be attributed to low standard of living in rural people and related factors.…”
Section: Discussionsupporting
confidence: 91%
“…The age groups with the greatest number of burn patients in this study were 21-30 years (33.9%) and 31-40 years (20.4%) old. This finding matches data from developing countries and differs from data in developed countries, where the largest age group is children aged 2-5 years [3,11]. Males accounted for 72% of patients, which corresponds with most reported studies [9,12,13], although some controversial findings have been published elsewhere [11,14,15].…”
Section: Risk Factorssupporting
confidence: 39%
“…This under reporting of the burn related mortality has major implications for planning, implementation and monitoring of prevention programmes. The descriptions in literature have also failed to present population-based mortality statistics limiting their usefulness to either monitor temporal changes in mortality in response to prevention programmes or to compare mortality across different geographic regions [16][17][18][19][20]. On the other hand studies that do report population-based statistics have suffered from a lack of consistency in presenting patient demographics, injury characteristics as well as age-and gender-specific injury rates [17,[21][22][23].…”
Section: Introductionmentioning
confidence: 90%